1998
DOI: 10.1177/000348949810700217
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous and Metachronous Multiple Primary Laryngeal Malignancies

Abstract: The article reviews the literature on synchronous and metachronous multiple primary malignant laryngeal tumors of the same phenotype, of different phenotypes, and of different histogenesis.The development of a second or even third primary cancer involving the same system is not uncommon. For instance, the association of cancer of the larynx with lung cancer has been increasing and can be explained by the presence of common pathogenetic factors acting in the respiratory system.Multiple primary carcinomas of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Two of our local recurrences were from a second primary within the larynx (contralateral vocal fold and ipsilateral supraglottis).The issue of multiple synchronous and metachronous primary laryngeal malignancy is discussed at length by Ferlito et al 31 . Fujita et al .found a second cancer developed in 22% of 158 patientstreated by radiotherapy for a T1 glottic cancer, 67% ofwhom developed one in the upper aero‐digestive tract 32 …”
Section: Discussionmentioning
confidence: 88%
“…Two of our local recurrences were from a second primary within the larynx (contralateral vocal fold and ipsilateral supraglottis).The issue of multiple synchronous and metachronous primary laryngeal malignancy is discussed at length by Ferlito et al 31 . Fujita et al .found a second cancer developed in 22% of 158 patientstreated by radiotherapy for a T1 glottic cancer, 67% ofwhom developed one in the upper aero‐digestive tract 32 …”
Section: Discussionmentioning
confidence: 88%
“…The incidence of multiple primary tumors in patients with head and neck malignancy has a reported risk of between 3% and 7% after treatment of the index tumor 2 . The annual risk of developing multiple primary in patients with upper aerodigestive tract squamous cell carcinoma is thought to be between 1.5% and 5.1% 20,37 …”
Section: Discussionmentioning
confidence: 99%
“…2 The annual risk of developing multiple primary in patients with upper aerodigestive tract squamous cell carcinoma is thought to be between 1.5% and 5.1%. 20,37 Reporting on the incidence of multiple primary tumors in esophageal malignancies, Poon et al 38 found 100 patients with these tumors in 1055 patients studied. Of these, 47 had synchronous and 43 had metachronous tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation